Encouraging healthier grocery purchases online: A randomised controlled trial and lessons learned. Issue 2 (4th May 2022) - Bunten, Amanda; Shute, Becky; Golding, Sarah E.; Charlton, Caroline; Porter, Lucy; Willis, Zachary; Gold, Natalie; Saei, Ayoub; Tempest, Bethan; Sritharan, Nilani; Arambepola, Rohan; Yau, Amy; et al.
Abstract: Online supermarket platforms present an opportunity for encouraging healthier consumer purchases. A parallel, double‐blind randomised controlled trial tested whether promoting healthier products (e.g. lower fat and lower calorie) on the Sainsbury's online supermarket platform would increase purchases of those products. Participants were Nectar loyalty membership scheme cardholders who shopped online with Sainsbury's between 20th September and 10th October 2017. Intervention arm customers saw advertisement banners and recipe ingredient lists containing healthier versions of the products presented in control arm banners and ingredient lists. The primary outcome measure was purchases of healthier products. Additional outcome measures were banner clicks, purchases of standard products, overall purchases and energy (kcal) purchased. Sample sizes were small due to customers navigating the website differently than expected. The intervention encouraged purchases of some promoted healthier products (spaghetti [ B = 2.10, p < 0.001], spaghetti sauce [ B = 2.06, p < 0.001], spaghetti cheese [ B = 2.45, p = 0.001], sour cream [ B = 2.52, p < 0.001], fajita wraps [ B = 2.10, p < 0.001], fajita cheese [ B = 1.19, p < 0.001], bakery aisle products ( B = 3.05, p = 0.003) and cola aisle products [ B = 0.97, p < 0.002]) but not others (spaghetti mince, or products in the yogurt and ice cream aisles). There was little evidence of effects on banner clicks and energy purchased. Small sample sizes may affect the robustness of these findings. We discuss the benefits of collaborating to share expertise and implement a trial in a live commercial environment, alongside key learnings for future collaborative research in similar contexts.